Virtuálne meny (právna podstata, regulačný rámec a zdaňovanie) - Miroslav Štrkolec (Acta Universitatis Carolinae. Iuridica, 2022)
Virtual currencies have been part of economic reality for more than a decade but have only become the subject of legal regulation at European and national level in recent years. This is in a sense natural, since law as a normative system reacts only with a certain time lag to already existing facts, circumstances, and relations which, due to their impact, require legal regulation. The author deals with the legal nature of virtual currencies and their relationship to categories such as money, currency, crypto assets. The article then defines their regulatory framework and taxation in terms of de lege lata and de lege ferenda. The paper concludes with thoughts towards the future of virtual currencies in financial and tax law.